Talking responsibly about medicine in the Fourth Industrial Revolution - Alex Broadbent (The Thinker)
A lot of what is currently being said about the future of medicine in the fourth industrial revolution (4IR) is irresponsible: it appears to be uttered without regard for whether it is true or false. The philosopher Harry Frankfurt argues that we should define and use the word “bullshit” as a technical term to cover speech of this sort (Frankfurt, 2005).